Effects of L-carnitine supplementation for women with polycystic ovary syndrome: a systematic review and meta-analysis - Mohd Shukri, Mohd Falihin; Norhayati, Mohd Noor; Badrin, Salziyan; Abdul Kadir, Azidah (PeerJ, 2022)
Background Polycystic ovary syndrome (PCOS) is a disorder in reproductive age women and is characterized by hyperandrogenic anovulation and oligo-amenorrhea, which leads to infertility. Anovulation in PCOS is associated with low follicle-stimulating hormone levels and the arrest of antral follicle development in the final stages of maturation. L-carnitine (LC) plays a role in fatty acid metabolism, which is found to be lacking in PCOS patients. This systematic review and meta-analysis aimed to determine the effectiveness of LC supplementation for patients with PCOS. Methods We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Psychological Information Database (PsycINFO), and the World Health Organization International Clinical Trials Registry Platform for all randomized control trials, comparing LC alone or in combination with other standard treatments for the treatment of PCOS from inception till June 2021. We independently screened titles and abstracts to identify available trials, and complete texts of the trials were checked for eligibility. Data on the methods, interventions, outcomes, and risk of bias from the included trials were independently extracted by the authors. The estimation of risk ratios and mean differences with a 95 percent confidence interval (CI) was performed using a random-effects model. Results Nine studies with 995 participants were included in this review. Five comparison groups were involved. In one comparison group, LC reduced the fasting plasma glucose (FPG) (mean differences (MD) −5.10, 95% CI [−6.25 to −3.95]; P = 0.00001), serum low-density lipoprotein (LDL) (MD −25.00, 95% CI [−27.93 to −22.07]; P = 0.00001), serum total cholesterol (MD −21.00, 95% CI [−24.14 to −17.86]; P = 0.00001), and serum triglyceride (TG) (MD −9.00, 95% CI [−11.46 to −6.54]; P = 0.00001) with moderate certainty of evidence. Another comparison group demonstrated that LC lowers the LDL (MD −12.00, 95% CI [−15.80 to −8.20]; P = 0.00001), serum total cholesterol (MD −24.00, 95% CI [−27.61 to −20.39]; P = 0.00001), and serum TG (MD −19.00, 95% CI [−22.79 to −15.21]; P = 0.00001) with moderate certainty of evidence. Conclusion There was low to moderate certainty of evidence that LC improves Body Mass Index (BMI) and serum LDL, TG, and total cholesterol levels in women with PCOS.
Keywords: Carnitine; Polycystic ovary syndrome; Meta-analysis